African Developments: Sub-Saharan Africa, too, could achieve the Millennium Development Goals (MDGs) - Markus Loewe (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
2010 has been an important year for Africa. It marked the 50th anniversary of independence for 17 African countries and the 10th anniversary of the Millennium Declaration. It has also been around a decade since steps toward creating the AU und NEPAD were taken. In a series of DIE Briefing Papers, researchers from Europe and Africa look into African Developments a decade after the revival of the African Agenda to take stock and identify the challenges facing the continent in the years to come.
Keywords: 330